ANALYSIS OF THE ISSUES OF MODELING THE AIR TRAFFIC CONTROL PROCESS WITH INCREASING FLIGHT INTENSITY - Shukurova, Sabohat; Rustamov, Nozimzhon (Innovatsion texnologiyalar, 2024)
The air traffic control (ATC) process is a complex and dynamic system that ensures the safe and efficient operation of aircraft in the airspace. The ATC process involves various actors, such as pilots, controllers, airports, airlines and regulators, who communicate and coordinate their actions through various systems and procedures. The ATC process is influenced by many factors, such as weather, traffic, technical conditions, human factors and others. The ATC process is also subject to changes and uncertainties, such as increasing demand for air travel, technological innovations, environmental regulations and security threats. The main contribution of this article is to provide a comprehensive and integrated approach for modeling the ATC process with an increase in the intensity of flights. The article demonstrates the applicability and usefulness of the proposed models for supporting decision-making and policy making in the field of air traffic management. The article also identifies the challenges and limitations of the current ATC process and suggests directions for future research and development.